The evolution of scientific journal articles in periphery : a case study and analysis of the Raffles Bulletin of Zoology from 1928 to 2008. - Lin, Hui. (2011)
As an integral part of scientific communication, scientific journal articles play important role. The evolution of the scientific journal article has captured much attention and interest from researchers for understanding the changing practices and norms in scientific communities. So far most research on evolution of scientific journal articles focuses on scientific journals in the academic centre in European and American countries. This study undertook a case study of the Raffles Bulletin of Zoology (RBZ) from 1928 to 2008 in order to analyze the development of a scientific journal in academic periphery. A mixed-method design with a combination of quantitative and qualitative method was deployed in this case study. Quantitatively, statistics on various aspects of journal articles in RBZ were collected and analyzed. Qualitatively, schematic structures of journal articles in RBZ were coded and documented via Swales’ move analysis. Various factors that shaped the evolution of RBZ for the past 80 years were discussed, including change in the government policy, institutional change, change in scientific perspectives, editorial efforts, information organization and retrieval, as well as changing scientific communities. Under the various interwoven factors, RBZ underwent dramatic changes in a three-stage development, covering rudimentary period, transitional period and current period.